Coaching : approaches & perspectives - Cornett, Jake.; Knight, Jim. (Thousand Oaks, CA : Corwin Press, 2009)
Details various approaches to coach teachers and leaders in order to support teacher development and professional learning, and covers literacy, cognitive, instructional, content, classroom management, and leadership coaching.
Includes bibliographical references and index.
Teacher Librarian
Professional
Professional
Keywords: First-year teachers -- In-service training; Mentoring in education; Teachers -- In-service training; Mentoring; Teachers -- In-service training